Stakeholders' perceptions of ways to support decisions about health insurance marketplace enrollment: a qualitative study - A. J. Housten; K. Furtado; K. A. Kaphingst; C. Kebodeaux; T. McBride; B. Cusanno; M. C. Politi (BMC, 2016)
Abstract Background Approximately 29 million individuals are expected to enroll in health insurance using the Patient Protection and Affordable Care Act (ACA) Marketplace by 2022. Those seeking health insurance struggle to understand insurance options and choose a plan that best suits their needs. Methods We interviewed stakeholders to identify the challenges associated with the ACA Marketplace health insurance enrollment and elicited feedback about what to include in health insurance decision support tools. Interviews were transcribed and themes were identified using inductive thematic analysis. Results Stakeholders stated that consumers felt frustrated by unclear terminology, high plan costs, and complex calculations required to assess costs. Consumers felt anxious about making the wrong choice and being unable to change plans within a calendar year. Stakeholders recommended using plain language tables defining complex terms, grouping information, and using engaging graphics to communicate information about health insurance. Stakeholders thought that narratives of how others made decisions about insurance might be helpful to consumers, but recommended that they be tailored to the needs of specific consumers. Conclusion Strategies that clarify health insurance terms using plain language and graphics, acknowledge concern associated with making the wrong choice, calculate and enable cost comparison, and tailor information to consumers' unique needs could benefit those enrolling in ACA Marketplace plans, Narratives developed should be simple and inclusive enough for diverse populations.